Casting all your Anxieties on Him (1 Peter 5:7): Assessing the Impact of Spirituality on Mental Health - Sikhumbuzo Dube; Sinqobile Patience Sibanda (Pan-African Journal of Health and Environmental Science)
Creating an environment where re-engineering of the future of work in the post- COVID-19 era will be possible is invaluable. As church members try to make meaning of heart-wrenching situations, their spirituality is fundamental. This study assessed the effect of spirituality on mental health.       A theoretical approach was adopted, and related literature was employed to assess the impact of spirituality on mental well-being. It evaluates how one's connection to the divine can be soothing during troubling times. A brief theological analysis of 1 Peter 5:7, as it relates to cognitive and affective stability, forms an integral part. Re-engineering work in the post-COVID-19 era entails adopting therapies that depend on a higher power for sustenance to meet complex challenges, such as spiritually informed therapies including prayer. Mental health specialists and clergy can adopt flexible modern methods of care, integrating spirituality into mental health and harmonizing their activities.